Peningkatan Kewirausahaan Ekonomi Keluarga melalui Pemberdayaan UMKM - Wikantari, Maria Assumpta; Supriadi, Yudi Nur (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The development process is completely initiated by the public community in social activities to make it better is a process of empowerment. Therefore, the target community program is always involved in community empowerment. This is a very urgent process for improving the welfare of the community through improving the economy. One of them can be realized through increasing income activities from Micro, Small, and Medium Enterprises (MSMEs). The MSME empowerment process is implemented through Community Service (PKM) activities providing empirical ideas for real work for the advancement of MSMEs that are more independent. Economic empowerment through MSMEs can create an integrated unity between the role of the campus and the community, especially in RW 07, Padurenan Village, Tangerang City. However, there are problems faced by SMEs including a). Production is only in the manufacture of components or products, b) The lack of competence of SMEs in the application of technology c), Weak competence in the production and management process. Departing from the real problems and conditions, the role of MSMEs for the family economy is to increase the need for support from human resources, capital, media equipment, processes and marketing, and good use of natural resources and human resources. Therefore, the family economy can improve if it is seen in the increase in employment, income, always having assets, and meeting needs. Thus, it can be seen that the impact of the existence of MSMEs needs to provide benefits for the suitability of personal and corporate life. Therefore, MSMEs in RW 07 Padurenan Village, Tangerang City can improve the family's economy by being free from poverty to improve their standard of living